Effect of Technological alternatives in the mitigation of climate change in the aging of alpacas above 4,000 msnm Puno-Peru - Huanca Mamani, Tedosio (2019)
The objective of the study was to evaluate the effect of technological alternatives in the mitigation of climate change in the breeding of alpacas over 4,000 meters above sea level. The validation study was conducted in 06 farming communities of two agroecological zones of the Puno region. The variables under study were weight at birth, weight at weaning, weight of fleece, pregnancy and mortality percentage, during 2014 in which no technological alternatives were applied, while in 2015 and 2016 this set was applied of alternatives. The data were analyzed in a completely randomized design using the SAS statistical software version 9.4. The results show that the birth weights were of 6.01, 6.254 and 6.83 kg for the years 2014, 2015 and 2016 respectively (p <0.05). The weaning weights were of 29.02, 29.73 and 30.99 kg for the years 2014, 2015 and 2016 respectively (p <0.05). The fleece weights were 2.28, 2.35 and 2.75 kg for the years 2014, 2015 and 2016 respectively (p <0.05). The pregnancy percentages were of 68.33, 72.84 and 83.77 % in the years 2014, 2015 and 2016 respectively. The mortality percentages were 10.39, 5.11 and 2.44 % for the years 2014, 2015 and 2016 respectively (p<0.05). The set of technological alternatives applied during the years 2015 and 2016 had a significant effect on the birth weight, weaning weight, fleece weight, pregnancy percentage and mortality of the alpacas.